Penerapan Teknologi Budidaya Kedelai Desa Binaan Sentra Penghasil Kedelai di Leang-leang Kecamatan Bantimurung - Aminah Aminah; Yusriani Yusriani; St. Sabahannur; Marliana S Palad; Abd. Akbar; Muhammad Fadel (Sipakaraya : Jurnal Pengabdian Masyarakat, 2025)
This community service program aimed to apply research findings in the food sector to ensure soybean availability, enhance community independence and welfare, expand farmers’ knowledge of standardized soybean cultivation, and raise awareness of the nutritional importance of soybean milk in preventing stunting. The activity was carried out on September 10, 2025, in Leang-leang Village, Bantimurung District, Maros Regency, South Sulawesi, through counseling and technology guidance. The partners’ main problems included limited knowledge of cultivation, excessive use of chemical fertilizers, inefficient fertilization, repeated use of farm-saved seeds, limited capacity in seed production, and the inability to process harvests into value-added products. The results showed improved knowledge and skills of the Siparingerrang and Borongpaoe farmer groups in standardized soybean cultivation. Partners received a seed sorting machine to separate large and small seeds, as well as a push-type planter with 12 holes to increase efficiency. In addition, product diversification such as soybean milk, soybean flour, and tempe/tofu chips has the potential to increase farmers’ income and strengthen community food security.